Patriotisme dalam Puisi Risālah Ilā Jamāl ‘Abd al-Nāṣir Karya Nizār Qabbāni (Analisis Semiotika Riffaterre) - Mubarok, Iqbal; Mastur, Mastur; Irwansya, Irwansya (Universitas Muhammadiyah Gorontalo, 2024)
This study uses the material object of poetry Risa>lah Ila> Jama>l ‘Abd Al-Na>sir by Niza>r Qabba>ni using the formal object of Riffaterre's semiotics. The results of this study reveal that poetry Risa>lah Ila> Jama>l ‘Abd Al-Na>sir terms of heuristic reading, it is still scattered, fragmented, and not yet centralized. The retroactive or hermeneutical reading, in its actual hipogram, expresses a salutary homage to the first stanza indicated byDoves, ships and ferries the Nile with symbols accompanying them. as well as in the second stanza which reveals several questions, namely:In what era do you live?, In what era of inspirers?, And in what era of wizards? Which disassembled on this reading. The model in this poem is found in the sentences in each stanza. First pertama Kursiyyuka al-mahju>ru fī (minsyiyyatu al-bakri>) yabki> fa>risu al-ahla>m and the second Nuji>buhum: fi> asrin ‘abd al-nashir the first sentence that reflects a power and leadership, namely